Artistry in Bronze : The Greeks and Their Legacy XIXth International Congress on Ancient Bronzes - Spinelli, Ambra, 1982-; Lapatin, Kenneth D. S.; Daehner, Jens (Book collections on Project MUSE., 2017)
"The forty-seven papers in this volume derive from the proceedings of the nineteenth International Bronze Congress, held at the Getty Center and Villa in October 2015 in connection with the exhibition Power and Pathos: Bronze Sculpture of the Hellenistic World"--Provided by publisher.